A study of self-reported personal cannabis use and state legal status and associations with engagement in and perceptions of cannabis-impaired driving. (10th October 2022) - Brown, Timothy; Banz, Barbara; Schmitt, Rose; Gaffney, Gary; Milavetz, Gary; Camenga, Deepa; Li, Kaigang; Brooks-Russell, Ashley; Vaca, Federico
Abstract: Objective: The objectives of the current study were to (1) characterize predictors of perceived risk of driving within 2 h of cannabis use and driving after cannabis use in a sample of adults who have used cannabis in the past year and (2) determine whether the influence of these predictors vary by state legalizations status. Methods: Data for this study were from online surveys. Study participants from Colorado, Iowa, and Illinois were included if they reported being between 25 and 40 years old and had a history of cannabis use. Outcome variables included (1) days of cannabis use per month, (2) reported driving within 2 h of cannabis use (vs. not driving within 2 h as reference), (3) proportion of driving after cannabis use days per month (days of driving a car within 2 h of cannabis use per month/days of cannabis use per month), and (4) perception of safety of driving after cannabis use. Potential predictors included age of first use of cannabis, gender, education status, and state of residence. The SAS GLMSELECT Procedure was used for the analysis. Results: Increased age of first use of cannabis was associated with decreased days of cannabis use per month (B = −0.51 days/month per year), a reduction in the proportion of driving after cannabis use days per month (B = −0.02 per month), and decreased perception of safety of driving after cannabis use (B = −0.06 per year). Female gender was also associated with less use (B = −2.3 days per month), a lower proportion of driving following use (B = −0.06 days driving/days used), and decreased perception of safety (B = −0.29). In addition, residents of Colorado reported using the most days, had the highest likelihood of driving within 2 h of use, and had the most positive perceptions of being able to safely drive after cannabis use. Conclusions: The delay in onset of cannabis use may mitigate its use among adults and driving after cannabis use. This has important implications for driver safety. Intervention programs for reducing cannabis's effects on driving should focus on individuals with early onset of use, male drivers, and drivers in states where cannabis for adult recreational use is legalized.